Non-invasive continuous arterial pressure monitoring during transcatheter atrial fibrillation ablation: a feasibility prospective study. (19th May 2022) - Di Cori, A; Fiorentini, F; Parollo, M; Della Volpe, S; Mazzocchetti, L; Barletta, V; Segreti, L; Viani, S; De Lucia, R; Sarti, M; Bozzoli, D; Giannotti, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Transcatheter atrial fibrillation (AF) ablation is still carried out with continuous invasive radial arterial blood pressure (BP) monitoring in many centers. Continuous noninvasive blood pressure (CNBP) measurement using the volume-clamp method is a non invasive alternative method used in ICU. No data on CNBP reliability are available in the electrophysiology lab during AF ablation, where rhythm variations are common. Purpose: The objective of the present study was to compare continuous noninvasive arterial pressure measured with the ClearSight device with invasive radial artery pressure, used as the reference method during AF ablation. Methods: We prospectively enrolled 55 consecutive patients (age 62±11 years, 79% male) undergoing transcatheter AF ablation (62% paroxysmal, 38% persistent) at our center. Standard of care invasive BP monitoring via a radial cannula and a contro-lateral non-invasive finger volume-clamp continuous BP measurement device were positioned simultaneously in all patients for the entire procedure. Bland-Altman analysis was used to analyze agreement between the two techniques. Results: A total of 1219 paired measurements for systolic, diastolic, and mean arterial pressure were obtained in 55 subjects, with a mean (SD) of 22 (9) measurements per patient. Mean bias (SD) was -12, 97 (13, 89) mmHg for systolic pressure (level of agreement -14, 24–40, 20; correlation coefficient 0, 84), -1, 85 (8, 52) mmHg for diastolic pressure (level of agreement -18, 54–14, 84; correlation coefficient 0, 77) and 2, 31 (8, 75) mmHg for mean pressure (level of agreement -14, 84–19, 46; correlation coefficient 0, 85). Conclusion: In patients undergoing AF ablation, non-invasive finger volume-clamp continuous BP monitoring with the ClearSight device showed acceptable agreement with standard of care invasive BP monitoring. Larger studies are needed to confirm potential clinical implications of a continuous non-invasive BP monitoring during AF ablation.